Evaluation of Common Non-pharmacological Chemical Substance Poisonings in Childhood - Songül Ünüvar (Galenos Yayinevi, 2017)
Acute intoxications in adolescents and adults are mostly associated with intentional or accidental ingestions. Intoxications are commonly seen in children aged between 1 and 5 years and most of the cases are associated with accidental intake. In most of the children, no clinical symptoms related to intoxication are observed or only mild effects can develop. The main route of drug elimination is through kidneys. Absolute clearance in children is often lower than in adults but weight-adjusted clearance is higher. Depending on more rapid elimination in children the plasma half-life of the drug might be shorter in children than in adults. A shorter elimination half-life means that plasma steady-state is achieved with repeated doses. It is important to prevent childhood intoxications, and the use of child-resistant packaging and adequate supervision together with the secure storage of household substances are the basis of prevention of accidental childhood intoxications. Intoxications represent one of the most common medical emergencies in children, and epidemiological characteristics vary in different countries. Therefore, special epidemiological surveillance is necessary for each country to determine the problem according to which preventive measures should be taken. Early awareness and taking appropriate therapeutic measures seems to be effective in the reduction of mortality rate. The major and most common non-pharmacological chemical intoxications in childhood have been reviewed here with the intent of helping health-care professionals, particularly pediatricians to recognize and reduce the risk of harmful childhood intoxications.